VP AND VS STRUCTURE OF THE YELLOWSTONE HOT SPOT FROM TELESEISMIC TOMOGRAPHY: EVIDENCE FOR AN UPPER MANTLE PLUME - Waite G.P.; Smith R.B.; Allen R.M. (My University, 2006)
The movement of the lithosphere over a stationary mantle magmatic source, often thought to be a mantle plume, explains key features of the 16 Ma Yellowstone-Snake River Plain volcanic system. However, the seismic signature of a Yellowstone plume has remained elusive because of the lack of adequate data. We employ new teleseismic P and S wave traveltime data to develop tomographic images of the Yellowstone hot spot upper mantle. The teleseismic data were recorded with two temporary seismograph arrays deployed in a 500 km by 600 km area centered on Yellowstone. Additional data from nearby regional seismic networks were incorporated into the data set. The VP and VS models reveal a strong low-velocity anomaly from ~50 to 200 km directly beneath the Yellowstone caldera and eastern Snake River Plain, as has been imaged in previous studies. Peak anomalies are -2.3% for VP and -5.5% for VS. A weaker, anomaly with a velocity perturbation of up to -1.0% VP and -2.5% VS continues to at least 400 km depth. This anomaly dips 30° from vertical, west-northwest to a location beneath the northern Rocky Mountains. We interpret the low-velocity body as a plume of upwelling hot, and possibly wet rock, from the mantle transition zone that promotes small-scale convection in the upper ~200 km of the mantle and long-lived volcanism. A high-velocity anomaly, 1.2% VP and 1.9% VS, is located at ~100 to 250 km depth southeast of Yellowstone and may represent a downwelling of colder, denser mantle material. Copyright 2006 by the American Geophysical Union.